ASETILASI PATI UWI KUNING (Dioscorea alata) DAN APLIKASINYA SEBAGAI MIKROENKAPSULAN ASAP CAIR - , RENI RETNOWATI; , Prof. Dr. Ir. Purnama Darmadji, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Yellow yam is one kind of yam which is utilization was limited, but it contains high levels of starch. The starch from yellow yam can be processed into modified starch using acetylation method which can be applied as encapsulant in food industries. One of food products that needs to be encapsulated is liquid smoke, because there are compounds in liquid smoke such as phenol, carbonyl, and acid which easily lost during storage. This research was aimed to know the potential of modified starch made from yellow yam as encapsulant in liquid smoke microencapsulation process and to know the comparison effect among soluble solids of liquid smoke redistillate with modified starch on the efficiency and the characteristics of microcapsules produced. This study uses pH variations of initial starch slurry between 7, 8, and 9 in the modified starch making process. The modified starch with the highest solubility then used as encapsulant on liquid smoke microencapsulation process. The microencapsulation used spray drying method with the ratio variations between soluble solids of liquid smoke redistillate and the modified starch were 1:3, 1:4, and 1:5. The efficiency and characteristics of microcapsules that was produced would be analyzed. The result showed that the highest solubility is in the modified starch that made with the initial pH of starch slurry was 8. The ratio variations between soluble solid of liquid smoke redistillate and modified starch affected the efficiency and characteristics of liquid smoke microcapsules. The more ratio of modified starch were added, it will increased of capsulled compounds (phenols, carbonyls, acids), acids levels, product recovery, and particle size of liquid smoke microcapsules, but content of phenol levels, carbonyl levels, and solubility is were lower.